Crystal structure of 4-[(3,5-dichlorophenyl)carbamoyl]butanoic acid, C11H11Cl2NO3 - Hanifa, B.; Muhammad, Sirajuddin; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C11H11Cl2NO3, monoclinic, P21/c (no. 14), a = 17.2336(3) Å, b = 4.9604(1) Å, c = 14.3696(3) Å, β = 100.970(2)°, V = 1205.95(4) Å3, Z = 4, Rgt(F) = 0.0313, wRref(F2) = 0.0848, T = 293(2) K.